Treatment of presumed Nocardia endophthalmitis and subretinal abscess with serial intravitreal amikacin injections and pars plana vitrectomy - Hojjatie, Sara L. (J Ophthalmic Inflamm Infect, 2020)
A 64-year-old man with a past medical history of liver transplantation on chronic immunosuppressive therapy presented with gradual worsening of vision over 2 months in his right eye. His recent history of Aspergillus and Nocardia pneumonia with positive bronchoalveolar lavage, in concert with vitritis and subretinal abscess, were concerning for endogenous endophthalmitis. A sputum culture and transbronchial lung biopsy stains grew Nocardia farcinica although aqueous humor sampling was negative. He was treated with four serial amikacin intravitreal injections over the course of 4 weeks. Pars plana vitrectomy for worsening macular traction and subsequent cataract surgery resulted in significant clinical and anatomic improvement of vision to 20/60 and consolidation of the subretinal abscess.